Effect of thermobalancing therapy on chronic prostatitis and chronic pelvic pain syndrome. (July 2017) - Allen, Simon; Aghajanyan, Ivan G
Background: Type-III chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is the most common type of prostatitis. Patients and methods: We ascertained the effect of 'thermobalancing' therapy (TT; using Dr Allen's therapeutic device (DATD)) on CP/CPPS. We measured National Institute of Health Chronic Prostatitis Symptom Index (NIH-CPSI) scores, prostatic volume (PV), and maximum urinary flow rate (Qmax ) in one group of 45 patients who underwent TT and a control group that did not have TT, and compared these parameters between groups. Results: Baseline evaluation (pretreatment) of both groups showed no significant difference with regard to age, NIH-CPSI score, PV or Qmax . Pain score decreased in both groups but, in the treatment group, the difference between scores was considerably higher (8.72:1) than that of the non-treatment group. TT decreased quality of life (QoL) significantly whereas, in the control group, it decreased QoL slightly. TT reduced PV significantly whereas, in the control group, PV increased. TT increased Qmax significantly in CP/CPPS patients whereas, in the control group, TT did not elicit a significant change in Qmax . Conclusions: Six-month TT with DATD: (a) reduces CP/CPPS symptoms and improves QoL; (b) reduces PV; (c) increases Qmax . TT could be effective treatment for CP/CPPS.